On the method for estimating technical coefficients of input-output analysis - Sy, Do Van; Tam, Bui The; Thieu, Nguyen Van (Journal of Computer Science and Cybernetics, 2015)
In this paper a new method is presented for estimating the technical coefficients of the input-output analysis model with six sectors by using  the statistical numerical data on the gross domestic product and the  final demand and solving the system of the linear programming problems. The computational results presented in this  paper are more precise than that of the others in the last time.